2015
DOI: 10.5505/agri.2015.66487
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Efficacy Of Transversus Abdominis Plane Block In Neonates And Early Infants For Colostomy And Reversal Of Colostomy

Abstract: ÖzetPediyatrik hastalarda ultrason eşliğinde transversus abdominis plan (TAP) bloğu anestezistler arasında popülarite kazanmaktadır. Kolostomi ve stomanın kapatılması sırasında 10 yenidoğan ve bebekte ultrason eşliğinde TAP bloğu olgu çalışmasını sunuyoruz. Hebbard tarafından tanımlanan klasik TAP uygulandı ve maksimum 1 ml/kg dozda %0.25 levobupivakain enjekte edildi. Yenidoğan Ağrı Ölçeği kullanılarak 24 saat boyunca ağrı skorları değerlendirildi. Hastaların hepsinde minimal hemodinamik değişikliklerle blok … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Levobupivacaine 0.25% can be administered with doses ranging up to 1 mL/kg [4,5,7,[12][13][14][15].These recommendations are rarely based on pharmacokinetic data. Previous studies with ropivacaine showed an influence of the injected volume on the effectiveness of regional anaesthesia [6,16] while no study investigated the influence of the injected volume of levobupivacaine during a TAP block.…”
Section: Discussionmentioning
confidence: 99%
“…Levobupivacaine 0.25% can be administered with doses ranging up to 1 mL/kg [4,5,7,[12][13][14][15].These recommendations are rarely based on pharmacokinetic data. Previous studies with ropivacaine showed an influence of the injected volume on the effectiveness of regional anaesthesia [6,16] while no study investigated the influence of the injected volume of levobupivacaine during a TAP block.…”
Section: Discussionmentioning
confidence: 99%